COMPARATIVE PHYTOCHEMISTRY AND ANTI- FUNGAL INFECTION STUDIES WITH ECONOMIC TREES Vachellia nilotica and Senegalia ataxacantha DISTRIBUTED WITHIN KATSINA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
The Vachellia nilotica and  Senegalia ataxacantha are native to various African nations. This investigation aimed to compare the phytochemistry with anti-fungal infection studies of these economic trees distributed within the Katsina state of Nigeria. The survey was done with some selected local government areas across the three senatorial zones in the state. Shoot parts samples of two different tree plant species were collected and then were separately processed into powdered form and phytochemistry was performed. Phytochemical screening of these plants indicated the presence of numerous bioactive compounds which include flavonoids, steroids, alkaloids, glycosides,  saponins, and tannins in the shoot parts of the plant species. Betamethasone dipropionate, Neomycin, Ketoconazole, and Clobetasol propionate were the major compositions of any antifungal therapy and were sourced from the chemical organic compounds. It could be of great interest for the Katsina State Government to consider these plant species as a good source of valuable raw materials for pharmaceutical industries to manage the plants and generate revenue.
Keywords: Vachellia nilotica; Senegalia ataxacantha; phytochemistry; Katsina state